The DOF-Domain Transcription Factor ZmDOF36 Positively Regulates Starch Synthesis in Transgenic Maize - Wu, Jiandong; Chen, Long; Chen, Mingchao; Zhou, Wei; Dong, Qing; Jiang, Haiyang; Cheng, Beijiu (Frontiers in Plant Science, 2019)
Starch synthesis is a complex process that influences crop yield and grain quality in maize. Many key enzymes have been identified in starch biosynthesis; however, the regulatory mechanisms have not been fully elucidated. In this study, we identified a DOF family gene, ZmDOF36, through transcriptome sequencing analysis. Real-time PCR indicated that ZmDOF36 was highly expressed in maize endosperm, with lower expression in leaves and tassels. ZmDOF36 is a typical DOF transcription factor that is localized to the nucleus and possesses transcriptional activation activity, and its transactivation domain is located in the C-terminus (amino acids 227-351). Overexpression of ZmDOF36 can increase starch content and decrease the contents of soluble sugars and reducing sugars. In addition, abnormal starch structure in transgenic maize was also observed by scanning electron microscopy (SEM). Furthermore, the expression levels of starch synthesis-related genes were up-regulated in ZmDOF36-expressing transgenic maize. ZmDOF36 was also shown to bind directly to the promoters of six starch biosynthesis genes, ZmAGPS1a, ZmAGPL1, ZmGBSSI, ZmSSIIa, ZmISA1, and ZmISA3 in yeast one-hybrid assays. Transient expression assays showed that ZmDOF36 can activate the expression of ZmGBSSI and ZmISA1 in tobacco leaves. Collectively, the results presented here suggest that ZmDOF36 acts as an important regulatory factor in starch synthesis, and could be helpful in devising strategies for modulating starch production in maize endosperm.